Secured Internet of Things (IoT) Model using Blockchain - Khan, Abdul Muneem; Oni, Fuad Hossain; Omar, Jabed; Noman, MD. Abdullah Al; Jamil, MD. Borhan Uz (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.